2019
DOI: 10.1186/s12884-019-2302-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring English speaking Muslim women’s first-time maternity experiences: a qualitative longitudinal interview study

Abstract: Background Muslim women of child-bearing age make up a fair part of the UK society, however, literature addressing their health needs or experiences of health services have not been extensively researched. The term ‘Muslim’ is often combined with ethnic group identity, rather than used to refer to people distinguished by beliefs or affiliations. Muslim women commonly observe certain religious and cultural practices during their maternity journey. The little research there is in this area suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…This paper presents findings from the third phase of a three-phase qualitative study that explored Muslim women’s experiences of motherhood while engaging with NHS maternity services [ 14 , 16 ]. This third phase explored HCPs experiences of providing maternity services for Muslim women in the UK.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This paper presents findings from the third phase of a three-phase qualitative study that explored Muslim women’s experiences of motherhood while engaging with NHS maternity services [ 14 , 16 ]. This third phase explored HCPs experiences of providing maternity services for Muslim women in the UK.…”
Section: Methodsmentioning
confidence: 99%
“…An interview guide was prepared by one of the authors (SH) based on a review of the initial analysis of data from Phases 1 and 2 of the study reported elsewhere [ 14 , 16 ]. Topics covered participants’ awareness of other cultures and religious beliefs, specific needs of Muslim women and good practice and training regarding care for Muslim women, full interview guide available in [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the women's comments were in relation to midwives specifically. It is therefore important to educate HCPs including midwives to increase awareness of Islam, the beliefs and birth customs, to develop culturally competent care and facilitate woman-centred care when caring for Muslim women [26,27]. Further challenges at the system level are improving verbal and non-verbal communication, increasing the availability of interpreters, and emphasising the importance of continuity of care [31].…”
Section: Discussionmentioning
confidence: 99%